9(x-2)=-6(4-x)+8

Simple and best practice solution for 9(x-2)=-6(4-x)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-2)=-6(4-x)+8 equation:


Simplifying
9(x + -2) = -6(4 + -1x) + 8

Reorder the terms:
9(-2 + x) = -6(4 + -1x) + 8
(-2 * 9 + x * 9) = -6(4 + -1x) + 8
(-18 + 9x) = -6(4 + -1x) + 8
-18 + 9x = (4 * -6 + -1x * -6) + 8
-18 + 9x = (-24 + 6x) + 8

Reorder the terms:
-18 + 9x = -24 + 8 + 6x

Combine like terms: -24 + 8 = -16
-18 + 9x = -16 + 6x

Solving
-18 + 9x = -16 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-18 + 9x + -6x = -16 + 6x + -6x

Combine like terms: 9x + -6x = 3x
-18 + 3x = -16 + 6x + -6x

Combine like terms: 6x + -6x = 0
-18 + 3x = -16 + 0
-18 + 3x = -16

Add '18' to each side of the equation.
-18 + 18 + 3x = -16 + 18

Combine like terms: -18 + 18 = 0
0 + 3x = -16 + 18
3x = -16 + 18

Combine like terms: -16 + 18 = 2
3x = 2

Divide each side by '3'.
x = 0.6666666667

Simplifying
x = 0.6666666667

See similar equations:

| -2.9x=31.2 | | 4+(x-3)=5-7 | | 1=10+3x | | 8(3x-5)-4(2x+3)=12 | | 25=4x-3 | | X+x/4=15 | | 5=15+2x | | 8=4x-2 | | 6xy-9yx+4xy= | | 5x*5y=32 | | a+5+2a-2= | | 5p-8=3(4-p) | | 17x^3-2x^2-20x+8=0 | | 4x-5x+y+6y= | | 5(x+2)=7 | | 10x+6=7x | | 8mn+2mn-6mn= | | pq-8pq+9pq= | | 92748727x=835295 | | 6ab-5ab= | | 3x^2+10=P | | 2x+2y=88 | | x2-5x=-9/4 | | 88-7x=29x+20 | | 3x+7=173-7x | | X=20-4y | | 109-3x=6-7x | | x=3.887482194 | | Y=2(6)-3 | | Y=2(4)-3 | | Y=2x(-2)-3 | | 2x^3+x+8=0 |

Equations solver categories